Lateral Branch of the Thoracodorsal Nerve (LaT Branch) Transfer for Biceps Reinnervation. Issue 3 (March 2018) - Schusterman, M. Asher; Jindal, Rishi; Unadkat, Jignesh V.; Spiess, Alexander M.
Abstract : Summary: In cases of significant upper extremity trauma, the thoracodorsal nerve is a reliable secondary option for the restoration of elbow flexion. In all previous descriptions, however, the entire nerve is transferred. We describe a case utilizing the lateral thoracodorsal nerve (LaT) branch for biceps reinnervation with an associated cadaver study. Transfer of the LaT branch to the biceps branch was performed on a patient who had sustained a traumatic brachial plexus injury that left him without elbow flexion. Also, 4 cadavers (8 upper extremities) were dissected to identify the bifurcation of the thoracodorsal nerve and confirm the feasibility of transferring the LaT branch to the biceps motor branch. Axon counts of the thoracodorsal proper, LaT branch, musculocutaneous proper, and the biceps branch were also obtained. A bifurcation of the thoracodorsal nerve was present in all cadaver specimens, with an average distance of 7.5 cm (range, 6.2–9.8 cm) from the insertion of the latissimus dorsi muscle. Axon counts revealed a donor-to-recipient ratio of 0.85:1. Follow-up of our patient at 1 year showed improvement of elbow flexion manual muscle testing grade from 0 to 4/5. Furthermore, electromyography at 1 year confirmed biceps reinnervation and showed normal readings of the latissimus compared with preoperative electromyography. Transfer of the LaT branch is a viable and minimally morbid option for biceps reinnervation after traumatic branchial plexus injury. Further follow-up of our patient and larger prospective studies are needed to understand the true potential of this nerve transfer. Abstract : Supplemental Digital Content is available in the text.